Clinical Characteristics of Neovascular Age-Related Macular Degeneration without Typical Drusen - Hiroyuki Kamao; Katsutoshi Goto; Kento Matsuno; Kenichi Mizukawa; Atsushi Miki; Junichi Kiryu (Journal of Ophthalmology)
Purpose. To evaluate the clinical characteristics of neovascular age-related macular degeneration (nAMD) patients without typical drusen. Methods. We retrospectively studied 165 eyes in 165 patients with treatment-naïve nAMD, including typical AMD and polypoidal choroidal vasculopathy (PCV). According to the fellow eye condition, the patients were divided into nAMD with and without typical drusen groups. Eyes with soft drusen or subretinal drusenoid deposits were classified into the nAMD with the typical drusen group. Smoking status and diagnoses of hypertension and diabetes were identified from hospital records and patient recall. We assessed best-corrected visual acuity (BCVA), central retinal thickness (CRT) at the fovea, subfoveal choroidal thickness (SFCT), and the number of injections received. Results. The nAMD without typical drusen group was significantly younger (77.9 ± 7.6 vs. 71.8 ± 8.3, P<0.001) and had thicker SFCT at baseline (207.9 ± 99.5 vs. 260.1 ± 113.2 μm, P=0.007) and a higher proportion of PCV (30.6 vs. 63.1%, P<0.001). The proportion of ever-smokers was significantly higher in the nAMD without typical drusen group (54.8 vs. 70.9%, P=0.036). There were no statistically significant differences in the proportion of patients with hypertension or diabetes; BCVA, CRT, or SFCT changes; or the number of injections between the nAMD with and without typical drusen groups. Conclusion. The clinical features of patients in the nAMD without typical drusen group were almost identical to those of pachychoroid-driven choroidal neovascularization (CNV) patients. The nAMD without typical drusen group had a significantly higher proportion of ever-smokers than the nAMD with typical drusen group. Smoking could be a risk factor for the development of pachychoroid-driven CNV.